The Influence of AudioVisual Media on Ecological Intelligence and Critical Reasoning Ability in Class V Social Studies Learning at SD Negeri 1 Kabunderan, Purbalingga Regency - Eko Waluyo Budi Utomo (Green Publisher, 2024)
Learning involves the active interaction of individuals with their environment, leading to behavioral changes. Effective learning encompasses being student-centered, promoting educational interaction, creating a pleasant learning atmosphere, using various methods, providing suitable materials, and ensuring a conducive environment and supporting facilities. This study aimed to improve critical thinking skills about the environment in elementary social studies by applying audio-visual learning media. Using a descriptive method with a quantitative approach, the research involved 32 grade V students from SD Negeri 1 Kabunderan, Purbalingga Regency. The results showed a significant relationship between the audio-visual learning model and ecological intelligence (p = 0.038) and between the audio-visual learning model and critical reasoning ability (p = 0.037). These findings indicate that audio-visual media effectively enhances both ecological awareness and critical thinking skills in elementary social studies learning.